The transformation of sociological criticism into comedy with satire narrative: The "Hababam Classroom" (Hababam Sinifi) sequels - Nizam, Feridun (IGI Global, 2023)
The aim of the study is to analyze the narrative structure with sociological criticism of the Hababam Classroom film series, which satirizes the education system in Turkey with all its stakeholders. The series consisting of six films between 1975 and 1981 was chosen as the sample. The basic assumption is that while the educational system is aimed to be satirically criticized, the narrative structure turns into comedy. As a matter of fact, the Hababam Classroom series has taken its place in the memories as the first cult works of the comedy genre in Turkish cinema. The study is based on the assumption that instead of an epic narrative in satirizing and criticizing the education system with all its stakeholders, the narrative structure turns into comedy due to the nature of the satirical tradition. As a result, this assumption was confirmed. © 2023, IGI Global. All rights reserved.